Symptomological identification of Citrus Psorosis Virus (CPsV) in citrus orchards of Northern Cyprus - T. Alas; A. Akın; İ. Kahramanoğlu (Труды по прикладной ботанике, генетике и селекции)
This study was conducted to perform symptomological identification of Citrus Psorosis Virus (CPsV) in Northern Cyprus. This is the oldest known citrus virus disease, which causes huge decrease in citrus fruits’ quality. The first symptoms of the disease were found in Florida and California in the 1890s. The most important and well known symptoms of CPsV are dehiscence and spalling of the trunk and branches of old trees. Chlorotic spotting and ringspot may also be caused on the leaves of infected young trees.There were reports not to kill the infected trees in the Mediterranean basin and America, but the disease leads to an important reduction in yield and fruit quality in time. Recent available verbal information among the farmers in Northern Cyprus claims that there is an increase in the symptoms of chlorotic spotting on leaves and spalling on tree trunks, which are thought to be caused by CPsV. Grafting is a common management technique on citrus trees in Northern Cyprus, where most of the varieties have been grafted on sour orange; and grafting is among the major ways of transmitting this virus, together with other mechanical practices.The results of the present study showed that the virus disease in different citrus species and varieties of Northern Cyprus are mostly symptomatic.  In the current work, citrus orchards which showed disease symptoms were all recorded and a detailed database was prepared for future molecular analyses. Thus, it is revealed that further molecular studies should be carried in order to perform a scientific investigation into the presence of this virus disease in Northern Cyprus and prove it molecularly.